Integration of Sunflower and Sorghum Water Extracts Applied Alone or in Combination With Reduced Doses of Chevalier for Weed Control in Wheat - AL-Behadili, Alaa A. J.; Fadhel, Laith Z. (Iraqi Journal of Science, 2023)
Field trial was conducted with the aim of utilizing extract of allelopathic crop to reduce the use of synthetic herbicides in wheat fields. Sorghum extract at 12 L /ha, sunflower extract at 12 L /ha, combination of sorghum and sunflower extracts at 12 L /ha and chevalier at 25, 50 and 100% of recommended dose were applied alone or in combination with each other. Weed free and weedy check treatments were included for comparison. The experiment was conducted in a randomized complete block design with three replications. The results showed that the recommended dose of chevalier treatment recorded lowest means of weed density 15.7, 23.7, 25.3 and 27.9 weeds m-2and weeds dry weight 13.4, 16.4, 23.3 and 29.2 g m-2 and gave highest percentage of weed control 71.4, 67.4, 64.3 and 63.0% after 60, 75, 95 and 115 days of planting respectively, without significant difference on the sorghum water extract + sunflower water extract at 12L/ha +50% of treatment. Also, the recommended dose of chevalier treatment had highest mean of number of spikes 368.6 spike m-2, grain yield 5.75 ton ha-1, biological yield 17.70 ton ha-1 and harvest index 32.55% without significant difference in the sorghum water + sunflower water extracts at 12L/ha +50% of treatment in the grain yield and biological yield also without significant difference on the sorghum water extract + sunflower water extract at 12 L/ha) +33% of recommended chevalier treatment in the grain yield and biological yield. We can conclude that the allelopathic effects of sorghum and sunflower extracts with chevalier herbicide at half dose gave positive results in weeds control while improving the grain yield of wheat without a significant difference with the spraying of the chevalier herbicide at full dose.These results were a clear indication that the presence of the extracts had a synergistic or cumulative additive role with the low doses of chevalier herbicide that contributed to raising its efficacy in weeds control.